Assessment of Poverty Levels in Kazakhstan: The Impact of Cash Income Deficiency - N. A. Khaustovich (Экономика: стратегия и практика, 2025)
Today, poverty remains a significant problem affecting various population groups and economic stability. Understanding the key determinants of poverty is an important prerequisite for developing effective poverty reduction strategies. This study aims to identify the relationship between the poverty level and the population’s monetary income, as well as to assess the regional features of its spread in Kazakhstan. The methodology is based on an analysis of statistical data for 2001-2023 collected from official data from the Bureau of National Statistics of the Republic of Kazakhstan, the World Bank, and the United Nations. The article uses descriptive statistical methods to study the dynamics of poverty and correlation and regression analysis to identify the relationship between poverty and indicators such as average nominal income per capita, Gini coefficient, unemployment rate and household size. The results showed significant regional differences in poverty levels, with the highest poverty rates observed in the Turkestan region (9%) and the Abai region (8%). Regression analysis confirmed a significant impact of the cash income deficit on the poverty rate (R2=0.86, p<0.01). A high correlation between the poverty rate and the Gini coefficient (0.89) was revealed, indicating a significant impact of income inequality. The prospects for further research include an in-depth analysis of the impact of educational attainment on poverty, a study of the impact of digital financial technologies on household incomes, and an assessment of the effectiveness of government programs to reduce poverty.